Collective Economic Decisions and the Discursive Dilemma - Carl Andreas Claussen; Øistein Røisland (Norges Bank, 2005)
Most economic decisions involve judgments. When decisions are taken collectively, various judgment aggregation problems may occur. Here we consider an aggregation problem called the discursive dilemma , which is characterized by an inconsistency between the aggregate judgment on the premises for a conclusion and the aggregate judgment on the conclusion itself. It thus matter for the decision whether the group uses a premise- or a conclusion-based decision- making procedure. The current literature, primarily within jurisprudence, philosophy, and social choice, consider aggregation of qualitative judgments on propositions. Most economic decisions, however, involve quantitative judgments on economic variables. We develop a framework that is suitable for analyzing the relevance of the discursive dilemma for economic decisions. Assuming that decisions are reached either through majority voting or by averaging, we find that the dilemma cannot be ruled out, except under some restrictive assumptions about the relationship between the premise-variables and the conclusion.
hdl:11250/2498439
Keywords: D71; E60; 330; collective economic decisions; judgment aggregation; inconsistency